2020
DOI: 10.1021/acs.jafc.9b06918
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Lycopene Cyclases Illustrates the Metabolic Pathway toward Lutein in Red Algal Seaweeds

Abstract: Carotenoids are essential phytonutrients synthesized by all photosynthetic organisms. Acyclic lycopene is the first branching point for carotenoid biosynthesis. Lycopene βand ε-cyclases (LCYB and LCYE, respectively) catalyze the cyclization of its open ends and direct the metabolic flux into different downstream branches. Carotenoids of the β,β-branch (e.g., β-carotene) are found in all photosynthetic organisms, but those of the β,ε-branch (e.g., lutein) are generally absent in cyanobacteria, heterokonts, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…Macrophytic red algae have both LCYB and LCYE enzymes while microphytic algae have only the enzyme LCYB [52]. Some other studies also suggested that, synthesis of δ-carotene, α-carotene and lutein are absent in some groups of algae-like Bacillariophyceae, Chrysophyceae, Phaeophyceae, Xanthophyceae, and some red algae, while the β-carotene occurs in majority groups of algae and other photosynthetic organisms [18,58]. Liang et al [79] reported that the amino acid sequences of LCYB and LCYE are significantly similar.…”
Section: Biosynthesis Of Carotenesmentioning
confidence: 99%
See 4 more Smart Citations
“…Macrophytic red algae have both LCYB and LCYE enzymes while microphytic algae have only the enzyme LCYB [52]. Some other studies also suggested that, synthesis of δ-carotene, α-carotene and lutein are absent in some groups of algae-like Bacillariophyceae, Chrysophyceae, Phaeophyceae, Xanthophyceae, and some red algae, while the β-carotene occurs in majority groups of algae and other photosynthetic organisms [18,58]. Liang et al [79] reported that the amino acid sequences of LCYB and LCYE are significantly similar.…”
Section: Biosynthesis Of Carotenesmentioning
confidence: 99%
“…In the case of red algae, Lohr et al [55] reported that both MVA and MEP pathways participate in the biosynthesis of IPP molecules. On the other hand, Deng et al [58] suggested that bioinformatics analyses are not able to characterize the genes for MVA pathway enzymes in red algae. Based on the existing ESTs, genome data, and phylogeny clustering analysis, Du et al [59] also reported that green algae and red algae received their plastid by primary endosymbiotic events with cyanobacteria, while brown algae obtained their plastid via secondary endosymbiotic event with red algae.…”
Section: Biosynthesis Of C 5 Isoprene Units (Ipp/dmapp)mentioning
confidence: 99%
See 3 more Smart Citations